Multivariable control of a pneumatic conveying system - Birk, Wolfgang (Luleå tekniska universitet, Signaler och system, 1999)
This licentiate thesis deals with a multivariable controller of a pneumatic conveying system. The industrial process used to illustrate design, analysis and implementation of a multivariable controller is the injection of fine coal into a blast furnace. In the blast furnace process, coke is replaced by fine coal because of economical and environmental reasons. The coal mass flow to the blast furnace becomes a crucial parameter for its operation and hence a control system should be in place to maintain a constant flow. An optimal multivariable linear-quadratic controller has been designed in order to replace the conventional PI-controllers, which were not able to reach the desired control objectives. The design is analyzed by deriving the sensitivity functions of the closed loop system to noise, disturbances and uncertainties. The multivariable controller is then validated through experiments and test operation at the coal injection plant at SSAB Tunnplåt AB in Luleå, Sweden. The reached performance improvements compared with the conventional PI-controllers account for up to 80%. Finally, the controller is combined with a gas-leakage detection system to the commercially available product SafePCI, which is now installed and in operation at SSAB Tunnplåt AB in Luleå, Sweden. Godkänd; 1999; 20061025 (ysko)